Street sex work and Canadian cities: resisting a dangerous order - Ferris, Shawna (The University of Alberta Press, 2015)
Canadian cities are striving for high safety ratings by eliminating crime, which includes "cleaning" urban areas of the street sex industry. Ironically, those same sex workers also want to live and work in a safe environment. Shawna Ferris interrogates sanitizing political agendas, analyzes exclusionary legislative and police initiatives, and examines media representations. She gives a voice to sex workers who are often pushed to the background, even by those who fight for them. In the name of urban safety and orderliness, street sex workers face stigma, racism, and ignorance. Their human rights are ignored, and some even lose their lives. Ferris aims to reveal the cultural dimensions of this discrimination through literary and art-critical theory, legal and sociological research, and activist intervention. This book has much to offer to educators and activists, sex workers and anti-violence organizations, and academics studying women, cultural, gender, or indigenous issues